2013
DOI: 10.5539/ijbm.v8n13p102
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Job Stress in Police Work in a Developing Country

Abstract: An attempt was made to determine which job events are perceived as significant sources of stress in police work. The Police Stress Inventory was developed based on the interviews with police staff and experts in police administration for this study. The questionnaire was administered to a random sample of 220 police personnel. The respondents rated the job situations as least stressful (0%) to most stressful (100%). They consider the organizational and social aspects of their job are more stressful especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 45 publications
0
23
0
1
Order By: Relevance
“…One expected organizational stressor reported by both genders was the low salary for a potentially high-risk job (Suresh et al, 2013), while we found it very interesting that the difficulty of working with colleagues was due to the lack of cooperation and confidence in their emotional and relational competence. Women perceived the lack of cooperation and professional recognition for their job as a critical element more than men, as already reported by Morash, Kwak and Haarr (2006).…”
mentioning
confidence: 56%
“…One expected organizational stressor reported by both genders was the low salary for a potentially high-risk job (Suresh et al, 2013), while we found it very interesting that the difficulty of working with colleagues was due to the lack of cooperation and confidence in their emotional and relational competence. Women perceived the lack of cooperation and professional recognition for their job as a critical element more than men, as already reported by Morash, Kwak and Haarr (2006).…”
mentioning
confidence: 56%
“…Additionally, police officers are expected to deliver excellent services and being sensitive to the needs of the community (Abdullah, 2010). Generally, although police provide excellent service to the public, the public always perceives police officers as an enemy (Suresh, Anantharaman, Angusamy, & Ganesan, 2013). Therefore, building a relationship with the public for effective community policing is poses as a challenge for police.…”
mentioning
confidence: 99%
“…Police job involves high-risk tasks (Abdullah, 2010;Patterson, 2009;Russell, 2014;Suresh et al, 2013). Police officers encounter various traumatic experiences that sandwiched them between death or life decisions (Patterson, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, some evidence suggests the organizational aspects of law enforcement work are more stressful for officers than the physical aspects of policing (Suresh, Anantharaman, Angusamy, & Ganesan, 2013). As such, research on the most stressful aspects of policing suggests law enforcement officers think occupational stressors such as work disrupting family life, lack of communication, lack of workload control, excessive work, and inadequate support as more stressful than policing itself (Collins & Gibbs, 2003).…”
Section: Literature Review On Law Enforcement Officer Health Wellnesmentioning
confidence: 99%